Legal Review of the Implementation of Human Rights in Handling Cases of Violence Against Women - Nuroini, Indi; Putra, Rengga Kusuma; Sjuhudi, Ichsan; Miano, Muhammad Ryan Ramadhani; Dwiprigitaningtias, Indah (Al-Adalah: Jurnal Hukum dan Politik Islam, 2025)
Violence against women constitutes a violation of human rights and reflects entrenched structural gender inequality. In Indonesia, despite the existence of Law No. 23/2004 on the Elimination of Domestic Violence and the ratification of the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW), significant challenges persist in the implementation of legal protections. This study aims to evaluate the effectiveness of existing legal frameworks in addressing violence against women and to identify necessary regulatory reforms. Utilizing a normative juridical method with statutory and conceptual approaches, the study analyzes the alignment of national laws with international human rights standards. It also assesses policy implementation by examining court rulings, institutional reports, and empirical data on victim protection outcomes. The findings reveal pervasive gender bias in both regulatory provisions and law enforcement practices, which undermines victims’ access to justice. Key obstacles include the absence of a gender-sensitive legal perspective, inadequate protection mechanisms, and the limited capacity of law enforcement personnel. The study concludes that comprehensive legal reform, capacity building, and integrating a human rights-based approach are essential to establishing a more inclusive and effective legal protection system for women in Indonesia.